Content Analysis through Keywords Analysis: The Representation of the Participants in Esperanza Aguirre’s Political Speeches - Duque, Eladio (Mediaciones Sociales, 2015)
In this article we apply the keywords analysis, typical of corpus linguistics, to content analysis of communication. The analysis explores the representations of the participants in a corpus of political speeches of Esperanza Aguirre, president of Madrid region from 2003 to 2012. To perform the analysis, we classify the keywords of the corpus according to their relation with the different types of participants. Then, the words grouped under each participant are analyzed to discover common lexical and grammatical features. As a result of the analysis, the new groups of words tell us about the details of the representation of each participant. These representations are not isolated, as demonstrated by many words related in their contexts to various participants.
Keywords: content analysis; political speeches; keywords; representations; participants; Esperanza Aguirre.